“Acorda Santa Maria”: um estudo sobre as estratégias coletivas de organização dos familiares das vítimas da boate Kiss - Peixoto, Priscila dos Santos (2014)
This study is a result of an ethnography research that was done during the period of 8 months following the different collective strategies of the Kiss disco victims families organization, Santa Maria, Rio Grande do Sul, Brazil. After the fire in the disco that took to death 242 young people with ages between 18 and 36 years old, the families started to meet in different initiatives aiming the social work, the fight for justice and a space to join the families and the survivors of the victims. From these attempts it was created an ONG, a Family Association and two social Movements which were studied by participant observation and open semistructured interviews. The observation identified the presence of a support net among the families of 12 victims that interact in these different groups, forming two subnets: of justice and solidarity, whose link has relative aspects to spiritual questions. The access to these support nets occurred by a key informant, militant and idealizer of two of the studied movements and sustainer of the others. Starting from a theoretical analysis of the Anthropology of Emotions, studying the nets of support, the research focus on the mourning, the different ways to deal with the loss and the spirituality. Therefore, it is broach the symbolical attempts of explaining the tragedy and the death through the formulation of presage of death, signs of the presence after the tragedy and strategies of communication with the children by religiosity, dreams and everyday coincidence. The title of this study is a word of order tuning by the families in their protests aiming justice which culminate in the creation of support nets.